HUMAN NATURE ACCORDING TO ABÅª YAZÄªD AL-BUSTÄ€MÄª - Kohar, Abdul kohar Abdul (Journal of Islamicate Studies, 2019)
This paper aims to explain the concept of Sufism AbÅ« YazÄ«d al-BustÄmÄ«. this Sufis is a philosophical Sufism, where his followers tend to pronouce the controvers expressions (shatahiyyÄt). The teachings or the concepts of this Sufism is close to the concept of Sufism of Husayn Ibn MansÅ«r al-HallÄj and the concept of Sufism Muhy al-DÄ«n Ibn 'ArabÄ«. The first level of the his concept called FanÄ` and BaqÄ` then ittiá¸¥Äd. The difference between the concept of Sufism Husayn Ibn MansÅ«r al-HallÄj divided two human traits, namely human nature itself (al-nusÅ«s) and the nature of God also in humans (al-luhÅ«t), while the concept of Sufism AbÅ« YazÄ«d al-BustÄmÄ« called the concept of fanÄ', which teachs on how to eliminate the subtance of human nature (al-nusÅ«s) then what remains in man is only the nature of God (al-luhÅ«t) until the process of attaining what is called baqÄ'. Eliminating the nature of fanÄ' and prioritizing the nature of baqÄ' until in the end the person becomes holy, then God comes and there the unity between God and the servant that is called ittiá¸¥Äd, then it is the cause because he brings up his shatahiyyÄt. The study use the methode of literature review, with the presentation of qualitative-interpretative data, where the main object of researche is books and journals discuss about AbÅ« YazÄ«d al-BustÄmÄ«. This paper connclude that, According to AbÅ« YazÄ«d al-BustÄmÄ«, ittiá¸¥Äd is the peak of human nature. To find out how our nature as human beings, the authors assume that it is important to read and learn the concept of Sufism AbÅ« YazÄ«d al-BustÄmÄ«.